Comparison of Glecaprevir/Pibrentasvir and Sofosbuvir/Ledipasvir in Patients with Hepatitis C Virus Genotype 1 and 2 in South Korea - Shin, Hyun Deok; Song, Il Han; Lee, Sae Hwan; Kim, Hong Soo; Lee, Tae Hee; Eun, Hyuk Soo; Kim, Seok Hyun; Lee, Byung Seok; Chae, Hee Bok; Kim, Seok Hwan; Song, Myung Joon; Ko, Soon Yeong; et al. (The Korean journal of gastroenterology, 2024)
This study compared the effectiveness and safety of glecaprevir/pibrentasvir (GLE/PIB) and sofosbuvir/ledipasvir (SOF/LDV) in real-life clinical practice. The data from genotype 1 or 2 chronic hepatitis C patients treated with GLE/PIB or sofosbuvir + ribavirin or SOF/LDV in South Korea were collected retrospectively. The analysis included the treatment completion rate, sustained virologic response at 12 weeks (SVR12) test rate, treatment effectiveness, and adverse events. Seven hundred and eighty-two patients with genotype 1 or 2 chronic hepatitis C who were treated with GLE/PIB (n=575) or SOF/LDV (n=207) were included in this retrospective study. The baseline demographic and clinical characteristics revealed significant statistical differences in age, genotype, ascites, liver cirrhosis, and hepatocellular carcinoma between the GLE/PIB and SOF/LDV groups. Twenty-two patients did not complete the treatment protocol. The treatment completion rate was high for both regimens without statistical significance (97.7% vs. 95.7%, p=0.08). The overall SVR12 of intention-to-treat analysis was 81.2% vs. 80.7% without statistical significance (p=0.87). The overall SVR12 of per protocol analysis was 98.7% vs. 100% without statistical significance (p=0.14). Six patients treated with GLE/PIB experienced treatment failure. They were all male, genotype 2, and showed a negative hepatitis C virus RNA level at the end of treatment. Two patients treated with GLE/PIB stopped medication because of fever and abdominal discomfort. Both regimens had similar treatment completion rates, effectiveness, and safety profiles. Therefore, the SOF/LDV regimen can also be considered a viable DAA for the treatment of patients with genotype 1 or 2 chronic hepatitis C.